A polarizing microscopic analysis of the calcified masses based on their collagen fibre orientation in peripheral ossifying fibroma - Devi C Shetty; Aadithya B Urs; Puneet Ahuja; et al (Dove Medical Press, 2010)
Devi C Shetty1, Aadithya B Urs1, Puneet Ahuja2, Harish C Rai1, Seema Sikka1, Anshuta Sahu1, Yuthicka Sirohi11Department of Oral and Maxillofacial Pathology and Microbiology, I.T.S-CDSR, Muradnagar, Ghaziabad, Uttar Pradesh, India; 2ITS Dental College, Greater Noida, Uttar Pradesh, IndiaAbstract: Peripheral ossifying fibroma (POF) is a reactive gingival lesion exhibiting a diverse spectrum of histopathology, accounting for 9.6% of gingival lesions. This study encompasses a detailed clinical, radiographic, and histopathological analysis of 15 cases of POF, retrieved from departmental archives. The following cases were subsequently stained with a histochemical stain (van Gieson) and observed under a polarizing microscope. This study is an effort to analyze the diverse spectrum of mineralized components and their surrounding tissues. Clinically, the study revealed a female predilection (73%) with the second and third decade commonly affected. The most common site was interdental papilla of anterior region, presenting itself as pink and sessile nodular mass. Radiographic examination revealed 93% of the cases showing no manifestation on the radiograph. Histopathological analysis showed 73% of the cases exhibited a fibrocellular connective tissue stroma with plump fibroblasts around the mineralized areas. The collagen was predominantly mature. Polarizing microscopy of the mineralized tissue revealed that 53% of the cases showed only woven bone, 20% showed combination of lamellar bone and cellular cementum, 13.3% showed only cementum (cellular and acellular) with another 13.3% showing mixture of woven and lamellar bone. Thus, the concept/theory that POF develops from cells of PDL/periosteum is emphasized. The undifferentiated mesenchymal cells have an inherent proliferative potential and can form bone or cementum, whose nature can be confirmed by polarizing microscope. This origin from periodontal ligament can also account for the high recurrence rate seen in POF.Keywords: histogenesis, mineralized masses, polarizing microscopy